Exploring emic and etic perspectives on creative leadership - Ellan, Nadia (My University, 2021)
The aim of this research study was to explore emic and etic perceptions of creative leadership in the South African context, including exploring how creative leadership was defined, factors seen to promote and inhibit creativity in the workplace and the relationship between these and creativeleadership, and perspectives on good creative leadership. It was hoped that this would be useful to gain a greater understanding of different perspectives on creative leadership and to identify how these relate to the available literature as well as to gain information about how to facilitate good creative leadership and develop more innovative working environments practically. The sample for the study consisted of ten professionals working in creative industries who volunteered to be interviewed. Four employees and three managers working as marketing specialists or strategists represented emic perspectives on creative leadership, and three leadership specialists with expertise in creative leadership represented etic perspectives. The design for the study was qualitative and emergent and it was based in the interpretive paradigm.Individual semi-structured interviews were used to collect data from each participant. The data was analysed using Braun and Clark’s (2006) approach to thematic analysis. The findings from the research study indicated that creative leadership is a transformative form of leadership that was seen as very important in the workplace, especially with the rapid changescurrently taking place. Good creative leaders were seen as authentic and able to communicate with employees; the importance of creating a safe and conducive physical and psychological environment for employees to be creative was also emphasized. The participants also indicated that experience and practical training was very important for creative leadership. The information gathered provided a foundation for better understanding creative leadership in the South African context; and also supported identifying more theoretical and practical implicationsthrough further research on the topic
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts by Coursework and Research Report (in the field of Organisational Psychology) to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2021